Kepemilikan Keluarga, Tata Kelola Perusahaan, dan Audit Report Lag - Alvianti, Umi; Setiawan, Bambang Moertono; Rusmin, Rusmin; Astami, Emita Wahyu (E-Jurnal Akuntansi; Vol 31 No 11 (2021), 2021)
The governance of family companies is still a concern for investors and other stakeholders. This study examines the effect of family ownership and corporate governance on audit report lag (ARL). The research sample is a non-financial company with a dominant family ownership and listed on the Indonesia Stock Exchange for the 2017-2019 period. Using the usual least squares analysis method and multiple regression techniques, the results showed that family ownership and the number of commissioners were able to encourage auditors to complete audit reports faster. Meanwhile, the presence of independent commissioners and audit committees does not significantly affect ARL. Additional analysis enriches the research findings that there are unique characteristics in terms of monitoring and expropriation effects of family ownership on ARL that up to a certain level of ownership, family members carry out the supervisory function well and can issue audited financial reports more quickly. Keywords: Family Ownership; Board of Commissioners; Independent Commissioner; Audit Committee; Audit Report Lag.